Evaluation of the Contents of Manganese and Lead and their Hazard Indices in some Coffee Brands - Hamad Hasan,; Enaam Mohamed,; Rofeida Mohamed, (AlQalam Journal of Medical and Applied Sciences, 2026)
In this study Ten different coffee samples of different brands were collected from many Libyan Markets. The contents of Lead (Pb) and Manganese (Mn) were estimated in the selected samples by atomic absorption spectrometry (AAS). The concentrations of Manganese in the selected samples in this study fluctuated in the ranges of 0.100 and1.324 ppm. Whereas the concentrations of Lead ranged between 0.036 and 0.537 ppm. The higher concentration of Manganese was recorded in the Al Wasar Coffee sample, whereas the lower concentration of Mn was recorded in the Faysal coffee sample. On the other hand, the contents of Lead ranged between 0.036– 0.537ppm. The higher concentration of Lead was recorded in the Al-Wasar Coffee sample, while the lower ones were recorded in the Dubai Coffee sample. The study concluded that the contents of the selected coffee samples were higher than the limits recorded by WHO. The values of Estimated Daily Intake (EDI) ranged between 0.009 – 0.12 for manganese and from 0.003 to 0.048 for lead contents. On the side, the values (Estimated weekly Intake, EWI) for manganese ranged from 0.063 to 1.47 and from 0.021 to 0.336 for lead. On the other hand, the Target Hazard Quotient (THQ) values ranged from 0.0.0007 – 0.0095 for manganese and from 0.00031 – 0.0038 for lead. The results of these recorded high values of manganese contents are according to the safety limits.